Improving quality outcomes via process improvements and innovation: the largest single-surgeon series of 1,701 consecutive robotic lobectomy and segmentectomy cases - Cerfolio, Robert J.; Ostro, Natalie A.; McCormack, Ashley J. (Frontiers in Surgery, 2025)
ObjectivesOur goal is to continuously improve patient outcomes, care quality, and overall experience.MethodsThis is a quality improvement study based on the experience of a single surgeon and represents the world's largest reported consecutive series of robotic lobectomy and segmentectomy performed by a single surgeon.ResultsFrom 1 January 2009 to 31 December 2024, a total of 1,701 patients (52% women) were treated, of whom 1,138 underwent robotic lobectomy (1,094, 96.1% were completed robotically) and 563 patients underwent segmentectomy (561, 99.6% were completed robotically). Quality metrics improved over each quartile: conversion rates decreased from 13 patients in our first 62 operations to 1 in our last 600 patients (p < 0.001), 90-day mortality decreased from 0.3% to 0% (p < 0.001), and major morbidity decreased from 6% to 1% (p < 0.001). Among patients with cancer, 99% underwent an R0 resection, with a median of five N2 and two N1 lymph node stations resected, 24 lymph nodes removed, and blood loss of 20 cc. Efficiency metrics improved with medians as follows: length of stay decreased from 110 to 26 h (p < 0.001), operative times fell from 125 to 93 min (p < 0.001), chest tube duration decreased from 72 to 4 h, and patient satisfaction scores improved from 87% to 98%. Various selective process improvements and strategies that we implemented and, in our opinion, improved both patient outcomes and experience are shared to scale this experience to others.ConclusionsA commitment to getting better via innovation and process improvements of all aspects of the pre-, intra-, and postoperative care and their pathways leads to improved outcomes and patient experience for robotic pulmonary resection. The selective processes and strategies that we believe led to these improving outcomes are shared and are possibly scalable elsewhere.